ANALISIS PENGEMBANGAN INVESTASI PERALATAN RADIOLOGI DI RUMAH SAKIT UMUM RAJAWALI CITRA BANTUL YOGYAKARTA - Wahyudi, Nur; Rosyidah, . (Jurnal Kesehatan Masyarakat (Journal of Public Health), 2012)
Background: Investment is basically an effort of investing resources (capital) in business. The radiology unit in Rajawali Citra Hospital is cooperatively performed by the third party or an investment from the third party. The investment of the radiology tools has been performed for more than 5 years, yet a reliability study from the investment has been conducted. This study aimed at assessing the reliability of developing the investment of radiology tools in Rajawali Citra Hospital over 5 years Method: This study is a study with descriptive analysis method in quantitative and qualitative approach without using hypothesis. The subject of the study is parts of finance, radiology unit and medical support and financial balance of radiology in 2007 2011. The technique of data collection was interview and documentation of financial balance of the radiology unit. The data analysis was done descriptively by applying quantitative and qualitative analysis approach. Result: The result of the study from the financial aspect indicated that payback period (3 years) 327 was quicker than the economical value of the tools (5 years), NPV = Rp 5,252,878.3 investment was accepted because it resulted positive value, ARR = 150% investment was accepted because it provided more advantage than which has specified 100%, IRR = 15,2% investment was accepted because the result was more than the interest (10%), PI = 1,10 the investment was accepted because the result was more than 1. Conclusion: From the whole aspect in the reliability assessment of the investment such as market aspect, technology, law, management and financial resulted in positive value to the investment development of the radiology tools. Keywords: Investment, Reliability, Finance, Radiology.